2013
DOI: 10.1530/eje-12-0939
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between lactation duration and insulin and glucose response among women with prior gestational diabetes

Abstract: Background: Few studies have investigated whether favorable effects of lactation persist after weaning and protect women with prior gestational diabetes mellitus (GDM) against later development of insulin resistance and insulin secretion defects. Objective: To investigate the impact of lactation duration on insulin and glucose response among women with prior GDM. Design/methods: The study group comprised 144 women with a history of GDM between 2003 and 2010. Plasma insulin and glucose concentrations were obtai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
45
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 39 publications
4
45
1
Order By: Relevance
“…Exclusive or mostly (≤ 6 oz formula/24 h) breastfeeding was associated with lowering the prevalence of diabetes or prediabetes at 6-8 week postpartum in women who had GDM. Chouinard-Castonguay et al [25] observed that longer duration of lactation (≥ 10 months) is associated with improved insulin and glucose homeostasis in women with prior GDM at about 4 years after delivery. Ziegler et al [26] observed that the postpartum diabetes risk was lowest in women who breastfed for ≥ 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Exclusive or mostly (≤ 6 oz formula/24 h) breastfeeding was associated with lowering the prevalence of diabetes or prediabetes at 6-8 week postpartum in women who had GDM. Chouinard-Castonguay et al [25] observed that longer duration of lactation (≥ 10 months) is associated with improved insulin and glucose homeostasis in women with prior GDM at about 4 years after delivery. Ziegler et al [26] observed that the postpartum diabetes risk was lowest in women who breastfed for ≥ 3 months.…”
Section: Discussionmentioning
confidence: 99%
“…Women who report more than 9 cumulative months of breastfeeding over their reproductive lifetime are less likely to develop hypertension, hyperlipidemia, and metabolic syndrome 32, 33, 34, 35, 36, 37. Further, evidence suggests that a longer duration of breastfeeding is associated with a lower risk of developing type 2 diabetes mellitus,38, 39, 40, 41, 42, 43 and reduced maternal postpartum weight 44, 45, 46, 47…”
Section: Introductionmentioning
confidence: 99%
“…(3;4) Lactation duration has been associated with higher plasma HDL-cholesterol up to 2 years postpartum,(5;6) but others found no association with adipokines (leptin and adiponectin) at 3 years postpartum. (7;8) In women with recent gestational diabetes mellitus (GDM), lactation also has been associated with more favorable metabolic parameters during the postpartum period,(9–13) including lower plasma glucose (fasting and 2-hour), improved glucose tolerance, improved pancreatic β-cell function and higher HDL-cholesterol. Evidence is limited and conflicting about whether lactation exerts persistent effects on metabolism that may reduce future risk of type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%